2018
DOI: 10.1016/j.jebo.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Information (non)aggregation in markets with costly signal acquisition

Abstract: Abstract:Markets are often viewed as a tool for aggregating disparate private knowledge, a stance supported by past laboratory experiments. However, traders' acquisition cost of information has typically been ignored. Results from a laboratory experiment involving six treatments varying the cost of acquiring signals of an asset's value suggest that when information is costly, markets do not succeed in aggregating it. At an individual level, having information improves trading performance, but not enough to off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
(62 reference statements)
3
7
0
Order By: Relevance
“…Our findings indicate that prices partially aggregate the information in all treatments, which is compatible with the observed behavior in previous contributions in similar settings (Hey and Morone, 2004;Page and Siemroth, 2017;Corgnet et al, 2018), and laboratory asset markets with endogenous costly private information in general.…”
Section: Price Informativenesssupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings indicate that prices partially aggregate the information in all treatments, which is compatible with the observed behavior in previous contributions in similar settings (Hey and Morone, 2004;Page and Siemroth, 2017;Corgnet et al, 2018), and laboratory asset markets with endogenous costly private information in general.…”
Section: Price Informativenesssupporting
confidence: 89%
“…20 Inspired by Sunder (1992), a series of experimental studies explores the informational efficiency of prices in the presence of information acquisition, concluding that prices hardly reveal information when the distribution of (perfectly) informed traders is not common knowledge in the market Friedman, 1991, 1992;Camerer and Weigelt, 1991). More relevant for our experiment, several experiments analyze information aggregation in Arrow-Debreu asset markets with acquisition of imperfect information (Hey and Morone, 2004;Page and Siemroth, 2017;Corgnet et al, 2018;Halim et al, 2019). Generally, this strand of literature finds limited evidence that prices aggregate all information.…”
Section: Information Aggregationmentioning
confidence: 99%
“…While early empirical literature found support for the efficient market hypothesis (Fama, 1965, 1970; Scholes, 1972), subsequent research produced opposite evidence (De Bondt & Thaler, 1985; Ito et al., 1998; Jegadeesh & Titman, 1993). These mixed results extend to lab experimental studies where some have found evidence of “good” information aggregation (Camerer & Weigelt, 1991; Forsythe & Lundholm, 1990; Forsythe et al., 1992; Plott & Sunder, 1988) and some evidence of substantial divergence between market prices and underlying fundamentals (Corgnet et al., 2018, 2019; O'Brien & Srivastava, 1991; Page & Siemroth, 2018). One difficulty in understanding how well markets aggregate information is that there is no natural alternative institution to which we can compare the market's performance.…”
Section: Introductionsupporting
confidence: 52%
“…2 Finally, mispricing has also been observed in setups which allow for costly acquisition of private information (e.g. Huber, Angerer and Kirchler, 2011;Page and Siemroth, 2017;Corgnet, Deck, DeSantis and Porter 2018).…”
Section: Introductionmentioning
confidence: 99%